Understanding and comparison of self-reported problems of Syrian refugees in three countries. (30th September 2020) - Morina, N; Drescher, A; Akhtar, A; Spaaij, J; Kiselev, N
Abstract: Background: Syrian refugees have high levels of mental disorders. They face multiple stressors before, during and after migration which affect their psychosocial wellbeing. Stressors after flight may vary due to different geographic, economic, cultural, socio-political contexts. Previous studies demonstrate that displacement-related factors are as likely as war exposure to contribute to distress after migration and hence, are pivotal to include in public health policy. Assessments in mental health care are mainly through nomothetic measurements, often developed in western countries. A growing body of literature recognizes the importance of clients' own perspective, especially in cross-cultural settings. The aim of this multi-country study was to describe and compare self-reported problems of Syrian refugees between Jordan, Turkey and Switzerland. Methods: Using the semi-structured client-generated outcome measurement PSYCHLOPS enabled to identify and compare problems in various study settings: camp-based in Jordan (N = 61), community-based in Turkey (N = 46) and Switzerland (N = 57), respectively. Questionnaires were analyzed following thematic analysis. The developed coding framework allowed to qualitatively illustrate the meaning and quantitatively compare the frequency of codes. Results: Almost all the emerged themes are related to post-migration stressors. Over half of the participants reported practical problems with an emphasis on financial, employment, government regulations, followed by psychological and physical health problems. For participants in Turkey, finances are of much more concern than in Jordan and Switzerland, whereas in Switzerland, problems with government regulations stand out. Conclusions: This study underlines the importance of displacement-related factors with special regard to local key factors on psychosocial wellbeing. Consequently, when planning mental health care services and preventive measures such factors must be considered and addressed.